Folate transporter expression decreases in the human placenta throughout pregnancy and in pre-eclampsia - Williams, Paula Juliet; Mistry, Hiten D.; Morgan, Linda (Elsevier, 2012)
The transport of folate across the placenta involves a number of different receptors including folate receptor-alpha (FR-α), reduced folate carrier (RFC) and proton coupled folate transporter (PCFT). In addition there are a number of ATP-dependent transporters which have also recently been shown to be involved in folate transport; these include ABCB1, ABCC2 and BCRP (ABCG2). The aim of the current study was to characterise the placental mRNA and protein expression of these folate transporters throughout gestation and also to see if expression is altered in pre-eclampsia. Placental tissue was collected from women undergoing termination of pregnancy (TOP) and from women undergoing elective Caesarean section. To investigate mRNA expression quantitative real time PCR was used with gene specific oligonucleotide primers to FR-α, RFC, PCFT, ABCB1, ABCC2, BCRP and the reference gene YWHAZ. Protein expression was also characterised using immunohistochemistry of paraffin embedded placental tissue. Both protein and mRNA expression of all transporters examined decreased as the gestation progressed. Expression of FR-α and PCFT mRNA and protein were decreased in pre-eclampsia compared with normal term pregnancy. The higher levels of expression of FR-α, RFC, PCFT, ABCB1, ABCC2 and BCRP in early pregnancy indicate that these transporters may have an important role in the establishment and development of the placenta, with expression reducing in preparation for parturition. Reductions in FR-α and PCFT in pre-eclampsia may be a mechanism involved in the pathogenesis of pre-eclampsia by limiting placental folate uptake resulting in reduced levels of angiogenesis, cell proliferation and antioxidant protection.